The Third World charismat : Sheikh Mujib and the struggle for freedom - Khan, Zillur R. (Zillur Rahman), 1938- (Dhaka : University Press Ltd., 1996)
Political biography of Sheikh Mujibur Rahman, 1922-1975, former president of Bangladesh.
Includes bibliographical references (p. [239]-243) and index.
Keywords: Mujibur Rahman, -- Sheikh, -- 1920-1975.; Presidents -- Bangladesh -- Biography; Bangladesh -- Politics and government